On the preferences of principals and agents - Castillo, Marco; Petrie, Ragan; Torero, Máximo (Wiley, 2010)
One of the reasons why market economies are able to thrive is that they exploit the willingness of entrepreneurs to take risks that laborers might prefer to avoid. Markets work because they remunerate good judgment and punish mistakes. Indeed, modern contract theory is based on the assumption that principals are less risk averse than agents. We investigate if the risk preferences of entrepreneurs are different from those of laborers by implementing experiments with a random sample of the population in a fast‐growing, small‐manufacturing, economic cluster. As assumed by theory, we find that entrepreneurs are more likely to take risks than hired managers. These results are robust to the inclusion of a series of controls. This lends support to the idea that risk preferences is an important determinant of selection into occupations. Finally, our lotteries are good predictors of financial decisions, thus giving support to the external validity of our risk measures and experimental methods (JEL C93, D81, D86).